IMPACT OF INCOME-PAVING PRACTICES ON INCOME TAX APPLICATION STUDY OF A SAMPLE OF COMMERCIAL BANKS LISTED ON THE IRAQI STOCK EXCHANGE - M.M. Abbas Jalil Mohisen; M.M. Mohammed Abdul Amir Al – Ghazi (Scholar Express Journals, 2022)
The research aims mainly to find out whether there is a practice of preparing income in Iraqi commercial banks listed on the Iraqi Stock Exchange through the use of one of the modern measurement measures, the Miller model, as well as to know the impact of these practices on income tax for these banks, and to achieve this goal the research was applied to the United Investment Bank and Sumer Commercial Bank for the period (2019-2013) ) A range of financial and statistical methods such as regression, correlation factors and F, T testing have been used to test research hypotheses. For those banks. The research also concluded with a set of recommendations, the most important of which are: accounting standards officials should reduce the ability of management in income-generating practices by reducing the number of alternatives available in the field of measurement and financial reporting with controls for each alternative, as well as working to improve the transparency of financial statements through adequate and fair disclosure, and working to introduce the subject of accounting ethics as an independent subject within the curriculum of the Accounting Department in Iraqi universities and institutes
Keywords: Iraqi commercial banks; the Miller model